Red cell distribution width to albumin ratio is associated with asthma risk: a population-based study - Ding, Jinzhen; Zhang, Yixiang; Chen, Xiaoyang (Frontiers in Medicine, 2024)
The red cell distribution width to albumin ratio (RAR), a newly identified biomarker of inflammation, has been linked to a variety of inflammatory diseases.Asthma, a major burden on global health, is an inflammatory airway disease that is profoundly affected by inflammation. This study primarily sought to examine the influence of RAR on the risk of developing asthma.Methods: Data from 1999-2020 was gathered from the NHANES database. The impact of RAR on asthma risk and their nonlinear relationship were clarified by multivariate logit and restricted cubic spline (RCS) analyses. Subgroup and interaction analyses collectively formed the sensitivity analysis for this study.Results: This study was based on an analysis of 54,161 individuals. RAR has been identified as an independent risk factor for asthma, according to logit analysis. The moderate and high RAR groups had a 16% (95% confidence interval (CI): 1.06-1.27) and 43% (95% CI: 1.30-1.58) higher risk respectively, compared to the lowest group. Every 0.5 unit increase in RAR almost doubled the risk of asthma (odds ratio (OR):1.82, 95% CI: 1.55-2.12). There was no non-linear relationship between RAR and asthma risk, based on RCS analysis. Combining subgroup and interaction analyses results, all subgroups in this study showed consistent trends with the overall population.Notably, this article, the first to examine the relationship between RAR and asthma risk, unveiled a positive linear correlation between them. With an increase in RAR, whether analyzed as a categorical or continuous variable, asthma risk significantly increases. This finding was beneficial for clinicians to anticipate and assess the onset of asthma through stratified or dynamic management. Given RARs numerous advantages, its application in clinical settings held considerable promise.